Cationic dyeable polyester fiber at normal pressure and its preparation method
Patent Information
- Application Number
- CN202611262981.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]现有常压阳离子可染聚酯纤维在工业化生产及应用过程中仍存在以下问题:熔融纺丝阶段熔体黏度波动较大,纺丝稳定性不足;纤维染色后易出现染色不匀和染深性不足;纤维在高温加工及使用过程中色泽稳定性差,易发生黄变;纤维的拉伸强度和尺寸稳定性较常规聚酯纤维有所下降
[0015]This invention involves pre-esterifying isophthalic acid-5-sulfonate with polyethylene glycol to form a sulfonate-PEG esterified prepolymer, which is then co-condensed with the esterification products of purified terephthalic acid and ethylene glycol. This process encapsulates the polyethylene glycol segments at both ends within the adjacent sulfonate molecular structure via ester bonds. This structure prevents the catalytic degradation of the polyether segments by free terminal hydroxyl groups during high-temperature polycondensation, inhibits the decrease in melt intrinsic viscosity, and improves the stability of the melt spinning process and the durability of fiber color. Simultaneously, the intramolecular chemical bonds between the sulfonate groups and the polyethylene glycol segments ensure that the binding sites of cationic dyes are always surrounded by flexible ether diffusion channels, facilitating efficient dye migration to the binding sites under normal pressure boiling dyeing conditions.
Smart Images

Figure CN122918733A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyester fiber technology, and in particular to a cationic dyeable polyester fiber that can be dyed under normal pressure and its preparation method. Background Technology
[0002] Polyester fibers possess advantages such as high strength, dimensional stability, and good chemical resistance, making them the most produced type of synthetic fiber. Conventional polyethylene terephthalate (PET) has a regular molecular chain structure and lacks acidic groups that can bind to cationic dyes. Therefore, it can only be dyed with disperse dyes under high temperature and pressure conditions, which involves large investment in dyeing equipment, high energy consumption, and difficulty in obtaining the vibrant colors characteristic of cationic dyes. Developing polyester fibers that can be cationically dyed under normal pressure is an important direction in the field of polyester modification.
[0003] To impart cationic dyeability to polyester fibers, existing technologies typically introduce isophthalic acid-5-sulfonate as a third monomer into the polyester molecular chain, utilizing the ionic bond between the sulfonic acid group and the cationic dye to achieve dyeing. To further lower the dyeing temperature to atmospheric pressure boiling conditions, existing technologies also introduce polyethylene glycol as a fourth monomer, utilizing the polyethylene glycol chain segment to lower the glass transition temperature of the polyester and widen the dye diffusion channels, forming atmospheric pressure cationic dyeable polyester fibers.
[0004] Existing atmospheric pressure cationic dyeable polyester fibers still face the following problems in industrial production and application: large fluctuations in melt viscosity during melt spinning, resulting in insufficient spinning stability; uneven dyeing and insufficient dyeing depth after dyeing; poor color stability and susceptibility to yellowing during high-temperature processing and use; and decreased tensile strength and dimensional stability compared to conventional polyester fibers. These problems limit the further promotion and application of atmospheric pressure cationic dyeable polyester fibers. Summary of the Invention
[0005] In view of the above problems, a cationic dyeable polyester fiber that can be dyed at room pressure and a method for preparing the same are proposed to overcome or at least partially solve the above problems, comprising: Isophthalic acid-5-sulfonate was esterified with polyethylene glycol to prepare sulfonate-PEG esterified prepolymer. The counterions of isophthalic acid-5-sulfonate were lithium ions and sodium ions, and the molar ratio of lithium ions to sodium ions was 0.5:1 to 1:1. Purified terephthalic acid was esterified with ethylene glycol at 230-260℃ to obtain the esterified product. A copolyester was prepared by mixing sulfonate-PEG esterified prepolymer, esterification product, antimony / titanium composite catalyst, triphenyl phosphate, hindered phenolic antioxidant and nano-inorganic oxide nucleating agent and carrying out polycondensation reaction at 260~290℃ under vacuum conditions. The copolyester was melt-spun at 270~290℃ to obtain cationic dyeable polyester fiber under normal pressure. The acid component consists of purified terephthalic acid and isophthalic acid-5-sulfonate, accounting for 2-8 mol% of the total acid component. The number average molecular weight of polyethylene glycol is 200-1000, and polyethylene glycol accounts for 1-5 wt% of the total mass of the copolyester. The ratio of the total number of ether oxygen units to the total number of sulfonate groups in the copolyester is 4:1-8:1. The nano-inorganic oxide nucleating agent accounts for 0.05-0.50 wt% of the total mass of the copolyester. The nano-inorganic oxide nucleating agent is one of nano-SiO2 nucleating agent and nano-Al2O3 nucleating agent.
[0006] Preferably, in the esterification reaction, isophthalic acid-5-sulfonate reacts with polyethylene glycol at 170~210°C for 1~2 hours.
[0007] Preferably, the esterification rate of purified terephthalic acid and ethylene glycol reaches 95% or higher.
[0008] Preferably, the vacuum pressure for the polycondensation reaction is 30~80 Pa.
[0009] Preferably, the average particle size of the nano-inorganic oxide nucleating agent is 10~200nm.
[0010] Preferably, in the sulfonate-PEG esterified prepolymer, the molar ratio of isophthalic acid-5-sulfonate to polyethylene glycol is 2:1 to 2.2:1.
[0011] Preferably, the copolyester is dried before melt spinning.
[0012] Preferably, when esterifying purified terephthalic acid with ethylene glycol, a fifth monomer is also added, which is one of 1,3-propanediol and neopentyl glycol, accounting for 1 to 5 mol of the total diol component.
[0013] Preferably, the antimony / titanium composite catalyst accounts for 0.01~0.05 wt% of the total mass of the copolyester.
[0014] The present invention also provides a cationic dyeable polyester fiber that can be dyed under normal pressure, which is prepared by the preparation method of any one of the above claims.
[0015] This invention involves pre-esterifying isophthalic acid-5-sulfonate with polyethylene glycol to form a sulfonate-PEG esterified prepolymer, which is then co-condensed with the esterification products of purified terephthalic acid and ethylene glycol. This process encapsulates the polyethylene glycol segments at both ends within the adjacent sulfonate molecular structure via ester bonds. This structure prevents the catalytic degradation of the polyether segments by free terminal hydroxyl groups during high-temperature polycondensation, inhibits the decrease in melt intrinsic viscosity, and improves the stability of the melt spinning process and the durability of fiber color. Simultaneously, the intramolecular chemical bonds between the sulfonate groups and the polyethylene glycol segments ensure that the binding sites of cationic dyes are always surrounded by flexible ether diffusion channels, facilitating efficient dye migration to the binding sites under normal pressure boiling dyeing conditions.
[0016] By employing a mixed counterion of lithium and sodium ions and controlling the ratio of the total number of ether oxygen units to the total number of sulfonate groups in the copolyester, a coordination saturation state is achieved between the sulfonate counterions and the polyethylene glycol ether oxygen, weakening the tendency of ion clusters to aggregate in the melt. This results in stable melt viscosity, reduced spinning pressure fluctuations, and uniform distribution of sulfonate sites on the fiber cross-section, improving dyeing uniformity and dyeing depth. Simultaneously, the polyethylene glycol segments are moderately anchored due to coordination, enhancing fiber heat resistance. The introduction of nano-inorganic oxide nucleating agents improves the crystalline structure of the copolyester, compensating for the loss of crystal integrity caused by the copolymerization of sulfonates and polyethylene glycol, ensuring fiber tensile strength and dimensional stability. These combined effects enable efficient dyeing under normal pressure conditions, with fiber dye uptake, color fastness, mechanical properties, and processing stability meeting the requirements for industrial applications. The preparation process is compatible with existing polyester spinning equipment. Attached Figure Description
[0017] To more clearly illustrate the technical solution of the present invention, the accompanying drawings used in the description of the present invention will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a flowchart of a method for preparing cationic dyeable polyester fibers under normal pressure, provided by an embodiment of the present invention. Detailed Implementation
[0019] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0020] Reference Figure 1 This invention provides a method for preparing cationic dyeable polyester fibers under normal pressure, which specifically includes: Isophthalic acid-5-sulfonate was esterified with polyethylene glycol to prepare sulfonate-PEG esterified prepolymer. The counterions of isophthalic acid-5-sulfonate were lithium ions and sodium ions, and the molar ratio of lithium ions to sodium ions was 0.5:1 to 1:1. Purified terephthalic acid was esterified with ethylene glycol at 230-260℃ to obtain the esterified product. A copolyester was prepared by mixing sulfonate-PEG esterified prepolymer, esterification product, antimony / titanium composite catalyst, triphenyl phosphate, hindered phenolic antioxidant and nano-inorganic oxide nucleating agent and carrying out polycondensation reaction at 260~290℃ under vacuum conditions. The copolyester was melt-spun at 270~290℃ to obtain cationic dyeable polyester fiber under normal pressure. The acid component consists of purified terephthalic acid and isophthalic acid-5-sulfonate, accounting for 2-8 mol% of the total acid component. The number average molecular weight of polyethylene glycol is 200-1000, and polyethylene glycol accounts for 1-5 wt% of the total mass of the copolyester. The ratio of the total number of ether oxygen units to the total number of sulfonate groups in the copolyester is 4:1-8:1. The nano-inorganic oxide nucleating agent accounts for 0.05-0.50 wt% of the total mass of the copolyester. The nano-inorganic oxide nucleating agent is one of nano-SiO2 nucleating agent and nano-Al2O3 nucleating agent.
[0021] In a preferred embodiment of the present invention, during the esterification reaction, isophthalic acid-5-sulfonate reacts with polyethylene glycol at 170~210°C for 1~2 hours.
[0022] In a preferred embodiment of the present invention, the esterification rate of the esterification reaction between purified terephthalic acid and ethylene glycol reaches 95% or more.
[0023] In a preferred embodiment of the present invention, the vacuum pressure of the polycondensation reaction is 30~80 Pa.
[0024] In a preferred embodiment of the present invention, the average particle size of the nano-inorganic oxide nucleating agent is 10~200 nm.
[0025] In a preferred embodiment of the present invention, the molar ratio of isophthalic acid-5-sulfonate to polyethylene glycol in the sulfonate-PEG esterified prepolymer is 2:1 to 2.2:1.
[0026] In a preferred embodiment of the present invention, the copolyester is dried before melt spinning.
[0027] In a preferred embodiment of the present invention, when esterifying purified terephthalic acid with ethylene glycol, a fifth monomer is also added. The fifth monomer is one of 1,3-propanediol and neopentyl glycol, accounting for 1 to 5 mol of the total diol component.
[0028] In a preferred embodiment of the present invention, the antimony / titanium composite catalyst accounts for 0.01 to 0.05 wt% of the total mass of the copolyester.
[0029] The present invention also provides a cationic dyeable polyester fiber that can be dyed under normal pressure, which is prepared by the preparation method of any one of the above claims. The above is the overall concept of the present invention. For ease of understanding, the following implementation details are added to the present invention: This invention provides a method for preparing cationic dyeable polyester fibers under normal pressure. The method first prepares a sulfonate-PEG esterified prepolymer, then completes the esterification of purified terephthalic acid and ethylene glycol, and then mixes the two esterification products with a polycondensation catalyst, a heat stabilizer, an antioxidant and a nucleating agent to carry out a polycondensation reaction, and finally obtains the fiber by melt spinning.
[0030] A search of known cationic dyeable polyester modification technologies reveals that while some reports mention adding oligomers containing sulfonate and polyethylene glycol segments as blending components to polyesters, no known technology involves pre-esterifying sulfonates and polyethylene glycol and then co-condensing them to covalently embed them into the polyester backbone. The essential difference between the sulfonate-PEG esterified prepolymer of this invention and known oligomers lies in the fact that the prepolymer of this invention contains reactive aromatic ester end groups, which are covalently embedded into the copolyester backbone through transesterification in the subsequent polycondensation stage, rather than being physically dispersed in the polyester matrix as a blending component. This prepolymer is not separated or purified before polycondensation; the unreacted isophthalic acid-5-sulfonate in the system continues to participate in polycondensation as a comonomer, ultimately forming a copolyester structure in which sulfonate groups and polyethylene glycol segments are adjacent within the molecular chain.
[0031] 5-Isophthalic acid sulfonate molecules contain two carboxyl groups and one sulfonate group, while polyethylene glycol molecules each contain a hydroxyl group at both ends. 5-Isophthalic acid sulfonate and polyethylene glycol are added to a pre-esterification reactor at a molar ratio of 2:1 to 2.2:1, along with an esterification catalyst. Tetraisopropyl titanate is used as the esterification catalyst, at a dosage of 0.01% to 0.05% of the total mass of 5-Isophthalic acid sulfonate and polyethylene glycol. Tetraisopropyl titanate is less sensitive to water than tetrabutyl titanate, and its catalytic activity is maintained for a longer time under conditions where water is generated during the esterification reaction. The byproduct isopropanol is easily removed by a nitrogen stream at the reaction temperature. If the reaction rate is low due to a high content of free sulfonic acid in the raw materials, the dosage of tetraisopropyl titanate can be increased to 0.05% to 0.08% of the total mass of 5-Isophthalic acid sulfonate and polyethylene glycol to compensate for the decrease in catalytic efficiency caused by coordination deactivation.
[0032] After adding the catalyst, the temperature is raised to 170℃ to 210℃ under nitrogen protection, and the reaction is carried out for 1 to 2 hours. The nitrogen flow rate is controlled at 50 ml to 200 ml of nitrogen per liter of reaction volume per minute (under standard conditions) to maintain the pressure inside the reactor at 0.01 MPa to 0.05 MPa (gauge pressure). Byproduct water vapor is carried out by the continuous nitrogen flow and captured by the condensation system. The endpoint of the prepolymer esterification reaction is determined by acid-base titration. When the acid value of the reaction system decreases to below 5 mg KOH / g, the esterification reaction is considered to have reached the endpoint.
[0033] The molar ratio of isophthalic acid-5-sulfonate to polyethylene glycol (PEG) is 2:1 to 2.2:1, causing the hydroxyl groups at both ends of each PEG molecule to esterify with the carboxyl groups of two isophthalic acid-5-sulfonate molecules. The free hydroxyl groups at both ends of the PEG segments are then blocked by aromatic ester bonds, resulting in a sulfonate-PEG esterified prepolymer. Unreacted isophthalic acid-5-sulfonate remains in the prepolymer system and continues to participate in copolymerization during subsequent polycondensation stages. Under high-temperature polycondensation conditions, the free terminal hydroxyl groups of PEG promote the cleavage of polyether segments, generating low-molecular-weight byproducts and reducing melt viscosity stability. After prepolymer formation, the ends of the PEG segments no longer exist as free hydroxyl groups, avoiding degradation of the polyether segments at high temperatures, reducing the decrease in melt intrinsic viscosity, and ensuring the color of the copolyester chips. Maintaining the pre-esterification temperature between 170°C and 210°C ensures that the esterification reaction proceeds fully while avoiding significant thermal decomposition of polyethylene glycol.
[0034] The counterion of 5-sulfoisophthalate is composed of lithium ions and sodium ions, with a molar ratio of lithium ions to sodium ions of 0.5:1 to 1:1. Lithium ions have a smaller radius than sodium ions, resulting in stronger coordination with the oxygen atoms of polyethylene glycol ethers. The mixed counterion forms the structural basis for ion-ether oxygen coordination in the prepolymer stage. Lithium 5-sulfoisophthalate can be prepared by neutralization reaction of 5-sulfoisophthalate and lithium hydroxide: 5-sulfoisophthalate is dispersed in deionized water, and an aqueous solution of lithium hydroxide is slowly added while stirring at room temperature. The reaction temperature is controlled between 20°C and 80°C, and the addition continues until the pH of the system reaches 6.5 to 7.5. Stirring continues for 30 to 60 minutes to ensure complete neutralization. The mixture is then filtered, washed with deionized water, dried until the water content is below 0.5 wt%, and ground to obtain lithium 5-sulfoisophthalate powder. Sodium isophthalic acid-5-sulfonate and lithium isophthalic acid-5-sulfonate are mechanically mixed at the required molar ratio before the preparation of the prepolymer. After mixing, they are added to the pre-esterification reactor together with polyethylene glycol.
[0035] The esterification reaction of purified terephthalic acid and ethylene glycol is carried out in an esterification reactor. The molar ratio of ethylene glycol to purified terephthalic acid is controlled at 1.8:1 to 2.2:1. Under nitrogen protection, the temperature is raised to 230°C to 260°C and the reaction is continued until the esterification rate reaches more than 95%, yielding a mixture of ethylene glycol terephthalate and its oligomers. After the esterification rate reaches more than 95%, the content of unreacted carboxyl groups in the system is at a low level, creating conditions for subsequent polycondensation to obtain a sufficiently high molecular weight. When a fifth monomer is added, it is either 1,3-propanediol or neopentyl glycol, accounting for 1 mol% to 5 mol% of the sum of ethylene glycol and the fifth monomer. The fifth monomer is added to the esterification reactor together with ethylene glycol and enters the polyester molecular chain as a comonomer during the esterification stage. The introduction of the fifth monomer reduces the regularity of the molecular chain, increases the dye diffusion channels, and improves the dyeing depth and levelness.
[0036] In the polycondensation reaction stage, a sulfonate-PEG esterified prepolymer, the esterification product of purified terephthalic acid and ethylene glycol, an antimony / titanium composite catalyst, triphenyl phosphate, a hindered phenolic antioxidant, and a nano-inorganic oxide nucleating agent are mixed. The sulfonate-PEG esterified prepolymer is a waxy solid or a highly viscous liquid at room temperature and is preheated to 60°C to 80°C before being added. The esterification product of purified terephthalic acid and ethylene glycol is cooled to 230°C to 240°C before being added to the prepolymer, at which temperature the esterification product maintains good fluidity. The two are mixed using mechanical stirring at a speed of 60 to 120 rpm for 20 to 40 minutes. After homogeneous mixing, the antimony / titanium composite catalyst, triphenyl phosphate, hindered phenolic antioxidant, and nano-inorganic oxide nucleating agent are added. The mixing process is carried out under nitrogen protection to prevent oxidation of the esterification product at high temperatures.
[0037] The antimony / titanium composite catalyst is composed of antimony glycolate and tetrabutyl titanate, with a mass ratio of antimony glycolate to tetrabutyl titanate of 1:1 to 3:1. The specific preparation method is as follows: antimony glycolate and tetrabutyl titanate are separately dispersed in ethylene glycol to prepare an ethylene glycol suspension with a mass fraction of 1% to 5%. Before use, the two suspensions are mixed evenly according to the ratio. The antimony / titanium composite catalyst accounts for 0.01wt% to 0.05wt% of the total mass of the copolyester. Triphenyl phosphate accounts for 0.01wt% to 0.10wt% of the total mass of the copolyester. The hindered phenolic antioxidant accounts for 0.01wt% to 0.50wt% of the total mass of the copolyester. The hindered phenolic antioxidant is preferably pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] or 2,6-di-tert-butyl-p-cresol, the chemical formula of which is BHT. The nano-inorganic oxide nucleating agent accounts for 0.05 wt% to 0.50 wt% of the total copolyester mass. The mixture is heated to 260℃ to 290℃, and a vacuum is gradually applied to maintain the pressure at 30 Pa to 80 Pa. The reaction is carried out for 2 to 4 hours to obtain the copolyester. During the polycondensation reaction, samples are taken every 30 minutes to measure the intrinsic viscosity. The reaction is terminated when the intrinsic viscosity of the copolyester reaches 0.55 dL / g to 0.70 dL / g. This intrinsic viscosity range ensures that the copolyester has sufficient molecular weight to support melt spinning, while avoiding the aggravation of thermal degradation side reactions due to excessive polycondensation time. Intrinsic viscosity decrease refers to the extent to which the intrinsic viscosity of the copolyester melt decreases due to degradation at high temperatures.
[0038] During polycondensation, the antimony / titanium composite catalyst promotes transesterification and condensation, leading to continuous chain growth. The titanium component exhibits high activity, contributing to shorter polycondensation time and improved chip color, while the antimony component provides stable catalytic activity. Triphenyl phosphate complexes with metal ions generated from the decomposition of sulfonates, inhibiting the hydrolysis of sulfonates at high temperatures and reducing end-group degradation. Hindered phenolic antioxidants provide hydrogen atoms to capture free radicals, inhibiting oxidative yellowing of the copolyester at high temperatures.
[0039] The surface modification of the nano-inorganic oxide nucleating agent is performed before use. The surface modification uses the silane coupling agent γ-aminopropyltriethoxysilane. The modification process is as follows: the nano-inorganic oxide nucleating agent is dispersed in a mixed solvent of ethanol and deionized water at a volume ratio of 9:1, and ultrasonically dispersed for 20 to 60 minutes. Then, γ-aminopropyltriethoxysilane is added, with the amount added being 1% to 3% of the mass of the nano-inorganic oxide nucleating agent. The mixture is stirred at 60°C to 80°C for 2 to 4 hours, filtered, washed with deionized water, dried at 80°C for 6 to 12 hours, and then ground to obtain the modified nano-inorganic oxide nucleating agent.
[0040] The modified nano-inorganic oxide nucleating agent was added to the polycondensation system in the form of an ethylene glycol suspension with a solid content of 5 wt% to 20 wt%. It was ultrasonically dispersed for 10 to 30 minutes before use. The nano-inorganic oxide nucleating agent provides a heterogeneous nucleation surface during the cooling and precipitation of the copolyester melt, lowers the nucleation free energy barrier, refines spherulites, and compensates for the loss of crystal integrity caused by the copolymerization of sulfonate and polyethylene glycol. The nano-inorganic oxide nucleating agent is one of nano-SiO2 nucleating agents or nano-Al2O3 nucleating agents, with an average particle size of 10 nm to 200 nm. Within this particle size range, the nanoparticles have sufficient specific surface area to provide nucleation sites and are not prone to significant agglomeration.
[0041] The acid component in the copolyester consists of purified terephthalic acid and isophthalic acid-5-sulfonate, with isophthalic acid-5-sulfonate accounting for 2 mol% to 8 mol% of the total acid component, preferably 3 mol% to 6 mol%. The number average molecular weight of polyethylene glycol is 200 to 1000, preferably 400 to 800, and polyethylene glycol accounts for 1 wt% to 5 wt% of the total mass of the copolyester. The ratio of the total number of ether oxygen units to the total number of sulfonate groups in the copolyester is controlled to be 4:1 to 8:1. The total number of ether oxygen units is calculated by multiplying the amount of polyethylene glycol by the number of ether oxygen units per molecule of polyethylene glycol, calculated by dividing the number average molecular weight of polyethylene glycol by 44; the total number of sulfonate groups is calculated based on the amount of isophthalic acid-5-sulfonate; dividing the two yields the ratio of the total number of ether oxygen units to the total number of sulfonate groups. For example, in Formulation 1, the number-average molecular weight of polyethylene glycol is 600, and each molecule of polyethylene glycol contains approximately 13.6 ether oxygen units. When the amount of polyethylene glycol used is 4.0 wt%, the ratio of the total number of ether oxygen units to the total number of sulfonate groups is approximately 7.8:1.
[0042] Alkali metal ions can form coordination structures with polyethylene glycol ether oxygen atoms. The saturation coordination number of sodium ions with ether oxygen is approximately 6, while the coordination number of lithium ions with ether oxygen is between 4 and 6. When the ratio of the total number of ether oxygen units to the total number of sulfonate groups is in the range of 4:1 to 8:1, each counterion is surrounded by a sufficient number of ether oxygen atoms to form a coordination layer. The counterions are coated by the ether oxygen coordination layer, the tendency of ion clusters between sulfonate groups is weakened, the melt viscosity is stable, and the distribution of sulfonate groups in the copolyester molecular chain tends to be uniform. The ether-oxygen coordination layer provides a moderate anchoring effect on the polyethylene glycol (PEG) segments. The flexible backbone of the PEG segments still provides the free volume required for dye diffusion in terms of mobility. The coordination between the ether-oxygen and the counterion forms physical cross-linking points locally. The two effects work together at different scales: the flexible segments ensure the diffusion of dye molecules into the fiber interior during normal pressure dyeing, and the local coordination sites inhibit the aggregation of ion clusters of sulfonate groups and limit the excessive relaxation of PEG segments at high temperatures. Thus, while reducing the glass transition temperature, PEG does not lead to a significant deterioration in the thermal and dimensional stability of the fiber.
[0043] After the polycondensation reaction, the copolyester melt is extruded in strip form using a melt pump. The strips are then cooled in a water bath at 20°C to 40°C. The extruded strips pass through a cooling section approximately 2m to 5m long, rapidly cooling the surface temperature to below 100°C. At this temperature, the hydrolysis reaction rate is extremely low, and the intrinsic viscosity of the copolyester does not decrease significantly during cooling. The cooled and solidified strips are then pelletized to obtain copolyester chips with a particle size of 2mm to 5mm. After pelletizing, the copolyester chips are centrifuged to remove surface moisture and then dried. The drying conditions are: pre-crystallization at 120°C for 2 hours, followed by drying at 140°C for 6 hours. These drying conditions are suitable for copolyesters with a glass transition temperature above 100°C. If the glass transition temperature is significantly lower due to a high polyethylene glycol content, the pre-crystallization temperature can be appropriately reduced to 100°C to 110°C, and the pre-crystallization time extended, ensuring that the chips do not stick together. The drying process reduces the moisture content of the chips, preventing the molecular weight from decreasing due to ester bond hydrolysis during melt spinning.
[0044] After drying, the copolyester chips are melt-extruded by a screw extruder. The temperature of each section of the screw gradually increases from the feeding section to the metering section. The melt is metered by a metering pump and then enters the spinning box. The spinning temperature is 270℃ to 290℃, preferably 275℃ to 285℃. After the melt is extruded from the spinneret, it is cooled and solidified by side blowing. After oiling, it is wound at a winding speed of 2500m / min to 4000m / min to obtain cationic dyeable polyester fibers under normal pressure. The winding speed of 2500m / min to 4000m / min is suitable for preparing POY or FDY products. When preparing FDY, a stretching and heat setting process can be added after spinning, with the first roller temperature at 75℃ to 90℃ and the second roller temperature at 110℃ to 140℃. When preparing POY, no post-stretching is required; the fibers are wound directly. Side blowing cooling allows the nascent fibers to solidify rapidly, and oiling imparts fiber bundles and smoothness, ensuring stability during the winding process. The present invention also provides the following embodiments and comparative examples: Formula 1: 0.97 mol purified terephthalic acid, 2.0 mol ethylene glycol, 0.03 mol isophthalic acid-5-sulfonate (lithium ion to sodium ion molar ratio in isophthalic acid-5-sulfonate is 0.8:1), polyethylene glycol number average molecular weight 600, polyethylene glycol amount is 4.0 wt% of the total copolyester mass, antimony / titanium composite catalyst amount is 0.03 wt% of the total copolyester mass, triphenyl phosphate amount is 0.08 wt% of the total copolyester mass, hindered phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], amount is 0.15 wt% of the total copolyester mass, nano-SiO2 nucleating agent average particle size 50 nm, amount is 0.20 wt% of the total copolyester mass. The total acid component is 1.00 mol, and isophthalic acid-5-sulfonate accounts for 3 mol of the total acid component. In the preparation stage of the sulfonate-PEG esterified prepolymer, 0.02 wt% tetraisopropyl titanate was added, and the reaction was carried out at 190℃ for 1.5 hours until the acid value dropped below 5 mg KOH / g, meeting the endpoint judgment standard. In the esterification stage of purified terephthalic acid and ethylene glycol, the reaction was carried out at 250℃ until the esterification rate reached 97%. In the polycondensation stage, the temperature was 280℃, the vacuum pressure was 50 Pa, and the reaction was carried out for 3 hours. During the polycondensation process, samples were taken every 30 minutes to measure the intrinsic viscosity. The reaction was terminated when the intrinsic viscosity reached 0.60 dL / g. The copolyester melt was cooled in a water bath and then pelletized. The pellets were pre-crystallized at 120℃ for 2 hours and dried at 140℃ for 6 hours before melt spinning at 280℃ at a winding speed of 3200 m / min. The resulting fibers were dyed with cationic dyes at 98℃ and normal pressure for 40 minutes, achieving a dye uptake of 96.8%. The fiber cross-section was uniformly dyed, and the washing fastness reached grade 4 and the light fastness reached grade 4 or higher. The dyeing temperature is 20°C to 30°C lower than the high-temperature and high-pressure dyeing temperature of conventional cationic dyeable polyester fibers.
[0045] Formula 2: 0.96 mol purified terephthalic acid, 2.1 mol ethylene glycol, 0.04 mol isophthalic acid-5-sulfonate (lithium ion to sodium ion molar ratio in isophthalic acid-5-sulfonate is 1:1), polyethylene glycol number-average molecular weight 800, polyethylene glycol dosage is 5 wt% of the total copolyester mass, antimony / titanium composite catalyst dosage is 0.04 wt% of the total copolyester mass, triphenyl phosphate dosage is 0.10 wt% of the total copolyester mass, hindered phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], dosage is 0.20 wt% of the total copolyester mass, nano-Al₂O₃ nucleating agent average particle size 80 nm, dosage is 0.30 wt% of the total copolyester mass. The total acid component is 1.00 mol, and isophthalic acid-5-sulfonate accounts for 4 mol of the total acid component. In the preparation stage of the sulfonate-PEG esterified prepolymer, 0.03 wt% tetraisopropyl titanate was added, and the reaction was carried out at 200℃ for 1.2 hours until the acid value dropped below 5 mg KOH / g, meeting the endpoint judgment standard. In the esterification stage of purified terephthalic acid and ethylene glycol, the reaction was carried out at 255℃ until the esterification rate reached 96%. In the polycondensation stage, the temperature was 285℃, the vacuum pressure was 60 Pa, and the reaction was carried out for 2.5 hours. During the polycondensation process, samples were taken every 30 minutes to measure the intrinsic viscosity. The reaction was terminated when the intrinsic viscosity reached 0.58 dL / g. The copolyester melt was cooled in a water bath and then pelletized. After drying, the pellets were melt-spun at 285℃ and a winding speed of 3500 m / min. The resulting fibers were dyed with cationic dyes at 98℃ and normal pressure for 40 minutes, achieving a dye uptake of 98.2%, a washing fastness of grade 4 or higher, and a light fastness of grade 4 or higher.
[0046] Formula 3: 0.97 mol purified terephthalic acid, 1.9 mol ethylene glycol, 0.06 mol neopentyl glycol, 0.03 mol isophthalic acid-5-sulfonate (lithium ion to sodium ion molar ratio in isophthalic acid-5-sulfonate is 0.5:1), polyethylene glycol number average molecular weight 400, polyethylene glycol amount is 2.5 wt% of the total copolyester mass, antimony / titanium composite catalyst amount is 0.02 wt% of the total copolyester mass, triphenyl phosphate amount is 0.06 wt% of the total copolyester mass, hindered phenolic antioxidant BHT is used, amount is 0.10 wt% of the total copolyester mass, nano-SiO2 nucleating agent average particle size 30 nm, amount is 0.15 wt% of the total copolyester mass. The total acid component is 1.00 mol, isophthalic acid-5-sulfonate accounts for 3 mol of the total acid component. Neopentyl glycol accounts for 3 mol of the sum of ethylene glycol and neopentyl glycol. In the preparation stage of the sulfonate-PEG esterified prepolymer, 0.01 wt% tetraisopropyl titanate was added, and the reaction was carried out at 180℃ for 1.8 hours. The acid value dropped below 5 mg KOH / g, meeting the endpoint judgment standard. In the esterification stage of purified terephthalic acid, ethylene glycol, and neopentyl glycol, the reaction was carried out at 245℃ until the esterification rate reached 96%. In the polycondensation stage, the temperature was 275℃, the vacuum pressure was 40 Pa, and the reaction was carried out for 3.5 hours. During the polycondensation process, samples were taken every 30 minutes to measure the intrinsic viscosity. The reaction was terminated when the intrinsic viscosity reached 0.55 dL / g. The copolyester melt was cooled in a water bath and then pelletized. After drying, the pellets were melt-spun at 275℃ and a winding speed of 2800 m / min. The resulting fibers were dyed with cationic dyes at 98℃ and normal pressure for 40 minutes, achieving a dye uptake of 96.8%, a wash fastness of grade 4, and a light fastness of grade 4 or higher. The dyeing rate of Formula 3 is the same as that of Formula 1, but the fifth monomer contained in Formula 3 further increases the dye diffusion channels, thus improving the levelness and color fastness of dark dyeing.
[0047] Comparative Example 1: Following the components and process of Formula 1, the counterion of isophthalic acid-5-sulfonate was replaced with a single sodium ion, and no lithium ions were added, while all other conditions remained the same. Comparative Example 1 is used to illustrate the effect of introducing lithium ions on improving the dispersion uniformity of sulfonate groups and the stability of melt viscosity. In this comparative example, the fluctuation amplitude of the current of the reactor agitator motor during the polycondensation reaction was larger than that of Formula 1, indicating a decrease in melt viscosity stability and a decrease in fiber dyeing uniformity.
[0048] Comparative Example 2: Following the components and process of Formula 1, the amount of polyethylene glycol was adjusted to achieve a ratio of ether oxygen units to sulfonate groups of 2:1, while keeping other conditions constant. Comparative Example 2 illustrates the necessity of maintaining an ether oxygen / sulfonate molar ratio within the range of 4:1 to 8:1 for achieving counterion coordination saturation. In this comparative example, counterion coordination was unsaturated, the degree of sulfonate group aggregation increased, the fluctuation amplitude of the current in the reactor agitator motor increased during the polycondensation reaction, and the uniformity and depth of fiber dyeing decreased.
[0049] Comparative Example 3: Following the components and amounts of Formula 1, without the sulfonate-PEG esterification prepolymer preparation step, isophthalic acid-5-sulfonate, polyethylene glycol, purified terephthalic acid, and ethylene glycol were simultaneously esterified and polycondensed in the same reactor, with all other conditions remaining consistent. Comparative Example 3 illustrates the effect of the in-situ copolymerization route of sulfonate-PEG prepolymer on inhibiting polyether segment degradation and improving chip color. In this comparative example, the copolyester chips were visually distinctly yellow, forming a identifiable difference from the light-colored chips of Formula 1. The intrinsic viscosity decreased more significantly before and after polycondensation. Under the same spinning conditions, the rate of pressure increase in the spinning assembly was faster than in Formula 1, and the breakage frequency increased during spinning.
[0050] In contrast, under the same process conditions, formulations one to three showed stable stirring current in the polycondensation reaction, light-colored or colorless transparent copolyester chips, significantly lower pressure rise rate in the spinning assembly compared to the comparative example, and significantly lower spinning breakage frequency compared to the comparative example. This indicates that the technical solution of the present invention has a clear improvement effect on all the problems pointed out by the comparative example.
[0051] The intrinsic viscosity of the mixture before and after polycondensation was determined using a conventional Ubbelohde viscometer method. The decrease in intrinsic viscosity was obtained by comparing the changes in intrinsic viscosity before and after polycondensation. Fiber breaking strength and elongation at break were tested using a conventional tensile testing machine. Spinnability parameters such as spinning breakage rate were statistically analyzed during actual spinning. These indicators were used to evaluate the thermal stability of the copolyester and the mechanical properties and processing stability of the fiber.
[0052] This invention involves pre-esterifying isophthalic acid-5-sulfonate with polyethylene glycol to form a sulfonate-PEG esterified prepolymer, which is then co-condensed with the esterification products of purified terephthalic acid and ethylene glycol. This process encapsulates the polyethylene glycol segments at both ends within the adjacent sulfonate molecular structure via ester bonds. This structure prevents the catalytic degradation of the polyether segments by free terminal hydroxyl groups during high-temperature polycondensation, inhibits the decrease in melt intrinsic viscosity, and improves the stability of the melt spinning process and the durability of fiber color. Simultaneously, the intramolecular chemical bonds between the sulfonate groups and the polyethylene glycol segments ensure that the binding sites of cationic dyes are always surrounded by flexible ether diffusion channels, facilitating efficient dye migration to the binding sites under normal pressure boiling dyeing conditions.
[0053] By employing a mixed counterion of lithium and sodium ions and controlling the ratio of the total number of ether oxygen units to the total number of sulfonate groups in the copolyester, a coordination saturation state is achieved between the sulfonate counterions and the polyethylene glycol ether oxygen, weakening the tendency of ion clusters to aggregate in the melt. This results in stable melt viscosity, reduced spinning pressure fluctuations, and uniform distribution of sulfonate sites on the fiber cross-section, improving dyeing uniformity and dyeing depth. Simultaneously, the polyethylene glycol segments are moderately anchored due to coordination, enhancing fiber heat resistance. The introduction of nano-inorganic oxide nucleating agents improves the crystalline structure of the copolyester, compensating for the loss of crystal integrity caused by the copolymerization of sulfonates and polyethylene glycol, ensuring fiber tensile strength and dimensional stability. These combined effects enable efficient dyeing under normal pressure conditions, with fiber dye uptake, color fastness, mechanical properties, and processing stability meeting the requirements for industrial applications. The preparation process is compatible with existing polyester spinning equipment.
[0054] The above provides a detailed description of a cationic dyeable polyester fiber that can be dyed at room pressure and its preparation method. Specific examples have been used to illustrate the principle and implementation of the invention. The description of the above examples is only for the purpose of helping to understand the method and core idea of the invention. At the same time, for those skilled in the art, there will be changes in the specific implementation and application scope based on the idea of the invention. Therefore, the content of this specification should not be construed as a limitation of the invention.
Claims
1. A method for preparing cationic dyeable polyester fibers under normal pressure, characterized in that, The method includes: Isophthalic acid-5-sulfonate is esterified with polyethylene glycol to prepare sulfonate-PEG esterified prepolymer, wherein the counterions of isophthalic acid-5-sulfonate are lithium ions and sodium ions, and the molar ratio of lithium ions to sodium ions is 0.5:1 to 1:
1. Purified terephthalic acid was esterified with ethylene glycol at 230-260℃ to obtain the esterified product. The sulfonate-PEG esterified prepolymer, the esterification product, the antimony / titanium composite catalyst, triphenyl phosphate, the hindered phenolic antioxidant and the nano-inorganic oxide nucleating agent are mixed and subjected to polycondensation reaction at 260~290℃ under vacuum to obtain a copolyester. The copolyester was melt-spun at 270~290℃ to obtain the cationic dyeable polyester fiber under normal pressure. The isophthalic acid-5-sulfonate accounts for 2-8 mol% of the total acid component, the acid component is composed of purified terephthalic acid and isophthalic acid-5-sulfonate, the number average molecular weight of the polyethylene glycol is 200-1000, the polyethylene glycol accounts for 1-5 wt% of the total mass of the copolyester, the ratio of the total number of ether oxygen units to the total number of sulfonate groups in the copolyester is 4:1-8:1, the nano-inorganic oxide nucleating agent accounts for 0.05-0.50 wt% of the total mass of the copolyester, and the nano-inorganic oxide nucleating agent is one of nano-SiO2 nucleating agent and nano-Al2O3 nucleating agent.
2. The method according to claim 1, characterized in that, In the esterification reaction, isophthalic acid-5-sulfonate reacts with polyethylene glycol at 170~210℃ for 1~2 hours.
3. The method according to claim 2, characterized in that, The esterification rate of the purified terephthalic acid and ethylene glycol esterification reaction reaches over 95%.
4. The method according to claim 3, characterized in that, The vacuum pressure for the polycondensation reaction is 30~80 Pa.
5. The method according to claim 4, characterized in that, The average particle size of the nano-inorganic oxide nucleating agent is 10~200nm.
6. The method according to claim 5, characterized in that, In the sulfonate-PEG esterified prepolymer, the molar ratio of isophthalic acid-5-sulfonate to polyethylene glycol is 2:1 to 2.2:
1.
7. The method according to claim 6, characterized in that, Before melt spinning, the copolyester is dried.
8. The method according to claim 7, characterized in that, When esterifying purified terephthalic acid with ethylene glycol, a fifth monomer is added, which is one of 1,3-propanediol and neopentyl glycol, accounting for 1 to 5 mol of the total diol component.
9. The method according to claim 8, characterized in that, The antimony / titanium composite catalyst accounts for 0.01~0.05 wt% of the total mass of the copolyester.
10. A cationic dyeable polyester fiber that can be dyed under normal pressure, characterized in that, The cationic dyeable polyester fiber under normal pressure is prepared by the preparation method according to any one of claims 1 to 9.